Mnożenie jednomianu przez sumę algebraiczną.
Proszę o szybką pomoc ;/

4(3x - 5) =
5(8m + 2) =
-2(5t + 8) =
-3(2a - 7) =
(15a + 20) : 5 =
(12p - 20) : 4 =
(-21m - 15) :3 =
(10t - 6) : (-2) =
12a +142=
20p - 55=
14p - 21-7=
-18x+24-3=
4(3a + 5) +3(5a - 2)=
2(7p - 3) - 5(3p - 1) =
-5(2 - 3m) - 2(m + 8) =
2x(3x - 4) + x(5 - 2x) =
3u(2 - 4u) - 5u(u+3) =
-5t(2t - 1) - 2t(3 - 5t) =
5x + 4 - 3(x - 6) =
-3z + 2 - 4(2z - 3) =
2y + 4(1 - 3y) =
3a - 1 - 2(3a - 6) =
-2x(x - 8y + 7) =
3(a + b) - 4(a - b) - 5(2a - 4b) =
2(3x - 4y + 5) - 3(-6x + 5y - 7) =
4a(2a - 3b + 9c - 12) =



Odpowiedź :

4(3x - 5) = 12x - 20

5(8m + 2) = 40m + 10

-2(5t + 8) = -10t -16

-3(2a - 7) = -6a + 21

(15a + 20) : 5 = 3a + 4

(12p - 20) : 5 = 12p-20/5

(-21m - 15) : 3 = -7m - 5

(10t - 6) : (-2) = -5t + 3

12a + 142 = 2(6a + 71)

20p - 55 = 5(4p - 11)

14p - 21-7 = 14(p - 2)

-18x + 24 - 3 = -3(6x - 7)

4(3a + 5) + 3(5a - 2) = 27a + 14

2(7p - 3) - 5(3p - 1) = -p - 1

-5(2 - 3m) - 2(m + 8) = -26 + 13m

2x(3x - 4) + x(5 - 2x) = x * (4x - 3)

3u(2 - 4u) - 5u(u+3) = u * (-9 - 17u)

-5t(2t - 1) - 2t(3 - 5t) = -t

5x + 4 - 3(x - 6) = 2x + 22

-3z + 2 - 4(2z - 3) = -11z + 14

2y + 4(1-3y) = 2(-5y + 2)

3a - 1 - 2(3a - 6) = -3a + 11

-2x(x - 8y + 7) = -2 x *potęga druga* + 16 x y - 14x

3(a + b) - 4(a - b) - 5(2a - 4b) = -11a + 27b

2(3x - 4y + 5) - 3(-6x + 5y - 7) = 24x - 23y + 31

4a(2a - 3b + 9c - 12) = 8a*potęga druga* - 12ab + 36 ac - 48a